Body composition and composition of gain of growing beef bulls fed rations with varying energy concentrations. (February 2022) - Honig, Aniela C.; Inhuber, Vivienne; Spiekers, Hubert; Windisch, Wilhelm; Götz, Kay-Uwe; Schuster, Manfred; Ettle, Thomas
Abstract: Data on chemical body composition of cattle serve as a basis for recommendations on energy and nutrient requirements. Relevant data of growing dual-purpose Fleckvieh (German Simmental) bulls are scarce and originate from old trials, covering low rates of gain and live weights. Hence, the aim of the study was to analyze the body tissue distribution, chemical composition, and composition of body weight gain of growing Fleckvieh bulls within a 120–780 kg live weight range. Results showed that body composition changed during growth but was not affected by dietary energy concentration. Changes in body composition were characterized by increasing shares of fat tissue and ether extract. Body tissues as blood, organs, gastrointestinal tract, and bone proportionately decreased during growth, while muscle and tendon proportions remained constant. The bulls featured enhanced growth potential and high muscle and protein gain throughout the described weight range. The requirements for metabolizable protein in relation to energy decrease with increasing live weight of the animals.